Extended Narrative Empathy: Poly-Narratives and the Practice of Open Defecation. Issue 4 (28th July 2016) - Clair, Robin Patric; Rastogi, Rahul; Blatchley, Ernest R.; Clawson, Rosalee A.; Erdmann, Charlotte; Lee, Seungyoon
Abstract: After reviewing empathy, narrative, and narrative empathy, the three concepts are combined to create a communication theory—Extended Narrative Empathy (ENE). The theory supports expanding perspectives via the collection of a rich array of narratives that are not always in agreement (poly-narratives). Empathy is required in order to see similar stories, peripheral stories, contentious stories, and antagonists as protagonists (via protagonist inversion) and overlapping of narratives as crucial to understanding complicated issues. The theory is discussed in light of open defecation in rural India.